Reticulate acropigmentation of dohi: A case report with insight into genodermatoses with mottled pigmentation - Deepak Mohana; Ujjwala Verma; Amarkant Jha Amar; R K P Choudhary (Wolters Kluwer Medknow Publications, 2012)
Reticulate acropigmentation of Dohi also called dyschromatosis symmetrica hereditaria or symmetrical dyschromatosis of the extremities is an autosomal dominant inherited disorder. It is characterized by mottled pigmentation with patchy depigmentation commonly over the back of the hands and feet and sometimes on the arms and legs